Analysis of metacognition skills with students' generalization abilities - Yani, Nur Fitri; Hendriana, Benny (Universitas Islam Negeri Raden Intan Lampung, 2021)
This research was conducted with the aim of describing metacognitive skills with students' mathematical generalization abilities in problem solving. This type of research is a qualitative descriptive research. This research was conducted on 9th grade students by taking 5 students as research subjects. Data collection techniques used in this research were tests, interviews, and questionnaires. The results of this research indicate that students are able to apply the designs that they will use to solve problems. Even though the evaluation indicators only review the results obtained.